АКАДЕМИЯЛЫҚ ЛИЦЕЙЛЕРДЕ Т.ҚАБУЛОВТЫҢ ӨМИРИ ҲӘМ ЛИРИКАСЫН ҮЙРЕНИЎ - Юсупов, Қ.А. (FAN va JAMIYAT, 2020)
The article deals with one of the actual issues - methods of teaching Karakalpak literature on the material of poetic works and creation of the famous Karakalpak poet- T.Kabulov to students of academic lyceums. The poet's works are rich according to their themes: love for Motherland, friendship, love, nature of homeland, ets. The author of the article recommends to use an effective technique-work in small groups in teaching the poet's lyrical works.